Jammu and Kashmir Post Article 370: A Comparative Overview of the Shifts (Global Journal of Human-Social Science, 2024)
This study explores how Jammu and Kashmir s terrain has changed since Article 370 was repealed and provides a thorough comparative analysis of the socio-political and economic aspects of the area The goal of the study is to offer important insights into the ramifications of this historic event by examining the complex developments that have occurred since the constitutional amendment A thorough analysis of the pre- and post-Article 370 abrogation periods is included in the comparative overview Using a multidisciplinary approach the study incorporates information from a range of sources including government documents and scholarly literature By utilizing a variety of research approaches the study aims to provide a comprehensive picture of the changes in Jammu and Kashmir
Keywords: dispute; conflict; article 370; shutdown; development; change